Guideline for Applying of Principal of Works H.M. King Bhumibol Adulyadej the Great for Community Based Tourism (CBT) Development of Highland Community in Maephrik Sub - district at Mae Suai District in Chiang Rai Province - Chantanupan, Raktibul (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The purposes of the research were to 1) study the context of Ban Pangtonphueng highland community, Maephrik Sub - district, Mae Suai District, Chiang Rai Province in tourism components (5As), 2) assess the potential for community - based tourism management, 3) apply the principles of works of His Majesty King Bhumibol Adulyadej the Great for community - based tourism development of Ban Pangtonphueng highland community, Maephrik Sub - district, Mae Suai District, Chiang Rai Province. The study employed a mixed method research combining qualitative and quantitative research approaches. The data was collected from 150 participants using a questionnaire and 37 participants using working group and semi - structured interviews to collect in - depth data by purposive sampling. The data collected through assessments are analyzed using descriptive statistics while data from working group and interviews are analyzed using content analysis. The research findings indicated that the Ban Pangtonphueng community is characterized by a natural landscape of highland area dominated by Assam tea forests. These forests remained verdant year - round. Every household primarily engages in Assam tea farming as their main occupation and maintains a traditional way of life, 67 housing 224 people. The village encompasses with tourism components 5As. Especially, attraction is the richness of the forest and a traditional tea - making practices with community - based tourism activities such as homestays. However, the community faces limitations in terms of inadequate facilities for accommodating tourists and a lack of knowledge and a tourism development plan. Nevertheless, the overall potential for community - based tourism management is assessed as high ( x= 3.67, S.D.= 0.684). The community can apply The Principal of Works H.M. King Bhumibol Aduladej, particularly the concept of "Explosion from within," to drive community - based tourism development through community participation, leading to sustainable community development.